Creating tangible interactions with cultural heritage: lessons learned from a large scale, long term co-design project. Issue 3 (2nd July 2020) - Avram, Gabriela; Ciolfi, Luigina; Maye, Laura
ABSTRACT: We reflect on the process, outcomes and value generated by applying co-design to a large scale, long-term (4 years) collaboration involving designers, developers and cultural heritage professionals, with the goal of creating a platform for the realisation of tangible interactive installations. The project was pioneering in establishing and sustaining co-design for the introduction of sector-changing technology into the museum domain. We gathered extensive data about the co-design process itself, including interviews investigating the participants' experiences and the impact on their practices. The paper provides insights from such case study, particularly with respect to value co-creation.